Psychological and Psychopathological Aspects of Kidney Transplantation: A Systematic Review - De Pasquale, Concetta; Pistorio, Maria Luisa; Veroux, Massimiliano; Indelicato, Luisa; Biffa, Gabriella; Bennardi, Nunzialinda; Zoncheddu, Pietro; Martinelli, Valentina; Giaquinta, Alessia; Veroux, Pierfrancesco (Frontiers in Psychiatry, 2020)
Kidney transplantation is a serious event that involves profound psychological, relational and social changes both for the patient and his family context. Assessment of personality profile, awareness of disease, family and social support of the patient candidate for kidney transplantation are necessary because factors not adequately considered, can influence the success of the transplant and alter the psychological stability of the patient. The present study aims to provide a systematic review of the literature of the last twelve years (2006-2018), focusing in particular on patient’s readiness level and illness management and on possible psychopathology. 62 studies were examined. Based on the Downs and Black checklist, most studies (n = 32) were of high quality; 15 of which related to lifestyle, health education and therapeutic adherence in post-renal transplantation, 17 studies concerned the possible existence of psychopathology and cognitive impairment of renal deceased transplanted subjects. The literature used has shown that the population of kidney transplant patients is exposed to a high risk of psychiatric disorders with repercussions on the quality of life and the risk of rejection. Therefore, an adequate pre-transplant psychosocial assessment is necessary, which allows a more in-depth knowledge of the candidate to plan coping strategies and possible post-transplant psychotherapy.